High Genetic Diversity of Plasmodium falciparum in the Low-Transmission Setting of the Kingdom of Eswatini. (4th July 2019) - Roh, Michelle E; Tessema, Sofonias K; Murphy, Maxwell; Nhlabathi, Nomcebo; Mkhonta, Nomcebo; Vilakati, Sibonakaliso; Ntshalintshali, Nyasatu; Saini, Manik; Maphalala, Gugu; Chen, Anna; Wilheim, Jordan; Prach, Lisa; et al.
Abstract: Background: To better understand transmission dynamics, we characterized Plasmodium falciparum genetic diversity in Eswatini, where transmission is low and sustained by importation. Methods: Twenty-six P. falciparum microsatellites were genotyped in 66% of confirmed cases (2014–2016; N = 582). Population and within-host diversity were used to characterize differences between imported and locally acquired infections. Logistic regression was used to assess the added value of diversity metrics to classify imported and local infections beyond epidemiology data alone. Results: Parasite population in Eswatini was highly diverse (expected heterozygosity [HE ] = 0.75) and complex: 67% polyclonal infections, mean multiplicity of infection (MOI) 2.2, and mean within-host infection fixation index (FWS ) 0.84. Imported cases had comparable diversity to local cases but exhibited higher MOI (2.4 vs 2.0; P = .004) and lower mean FWS (0.82 vs 0.85; P = .03). Addition of MOI and FWS to multivariate analyses did not increase discrimination between imported and local infections. Conclusions: In contrast to the common perception that P. falciparum diversity declines with decreasing transmission intensity, Eswatini isolates exhibited high parasite diversity consistent with high rates of malaria importation and limited local transmission. Estimates of malaria transmission intensity from genetic data need to consider the effect of importation, especially as countries near elimination. Abstract : In contrast to the commonly held perception that P. falciparum diversity declines with decreasing transmission intensity, infections from Eswatini exhibited high parasite diversity consistent with high rates of malaria importation and limited local transmission.